Form a proposal to audit the mutual operations with related parties program in accordance with international standards: Proposal pattern (Journal of Accounting and Financial Studies ( JAFS ), 2020)
The relationships between the related parties constitute a normal feature of trading and business processes. Entities may perform parts of their activities through subsidiary entities, joint ventures and associate entities. In these cases, the entity has the ability to influence the financial and operating policies of the investee through control, joint control or significant influence,  So could affect established knowledge of transactions and balances outstanding, including commitments, and relationships with related to the evaluation of its operations by users of financial statements, including the risks and opportunities facing the entity assess the parties. So research has gained importance of the importance of the availability of scrutiny of a proposed program takes into account the scrutiny Related party transactions and disclosures that are binding on the facility disclosed in accordance with local and international standards. Search based on the premise that the availability of an audit guide and auditing programs commensurate with the privacy of the transactions that take place between the relevant parties to help auditors in the performance of their work checksum and reduce the risk and impact of audit related to the financial statements of the parties. To achieve hypothesis sought to achieve its objectives in the application of a proposed audit program, it has reached a researcher to a group of the most important conclusions, the lack of scrutiny the program, whether the auditors' offices or in the Office of Federal Financial Supervisory includes the reliability of the financial statements of the entity.